Time management та огляд програмних застосунків - Коба, Ю. Ю. (ХНУРЕ, 2022)
This work was written to reveal the problem of lack of time of people in the modern world. Time is the most valuable resource that humanity now has, so it must be used wisely. Software developers have learned to use the best time management techniques in their own programs so that everyone can apply these useful advances in their daily lives. This not only makes our lives more productive, but also makes it much easier, as it reduces the level of stress on the nervous system, makes us calmer. That is why it is necessary to use all available resources to maintain a proper daily routine.
Keywords: Time management